THE IMPACT OF INTRAOPERATIVE NEUROPHYSIOLOGICAL MONITORING IN THYROID SURGERY ON THE CHOICE OF ANAESTHETIC AND RESUSCITATION OPTIONS - E.V. VOLKOV; L. KH. BATCHAEVA; V.V. FISHER; S.G. CHERNYSHYOVA (Avicenna Tajik State Medical University, 2022)
Objective: To assess the effect of intraoperative neurophysiological monitoring (IONM) on the incidence of life-threatening complications of the surgical treatment of thyroid diseases in the operating room and intensive care unit. Methods: A retrospective analysis of the medical records of 212 patients aged 31 to 72 was carried out. Depending on the treatment modality, they were divided into two groups. In group I (study group, n=96), IONM was used during surgery, and in group II (control group, n=116) - the surgery was performed without IONM. The effectiveness of IONM was assessed based on the number of complications and tracheal reintubation in the postoperative period. Results: IONM contributed to a statistically significant decrease in the number of postoperative complications. Thus, injury to the recurrent laryngeal nerve (RLN) was noted in 1 (1.0%) patient in the study group versus 17 (14.6%) in the control group (p<0.05); hoarseness was present in 3 (3.1%) and 35 (30.1%) cases in the study and control groups, respectively (p<0.05). In addition, although statistically insignificant, there was a reduced rate of tracheal reintubation: in two (2.1%) and (6.0%) patients in the study and the control groups, respectively (p>0.05). Of these, 5 (4.3%) patients needed surgeries due to bilateral injury to the RLN. The decrease in the incidence of complications, in turn, contributed to a reduction in both the average lengths of stays in the intensive care unit (6.2±0.5 days and 7.4±0.3 days in the study and the control groups, respectively, p>0.05) and the overall treatment time (59.1±1.7 and 121.3±4.8 patient days in the study and the control groups, respectively, p<0.05). Conclusion: IONM in thyroid surgery can reduce the number of complications, such as damage to the recurrent laryngeal nerve, although it does not exclude them entirely. The data obtained allow us to recommend using IONM in everyday practice.